The Density of Megabentos in Coral Reef Ecosystems in The Waters of Pongok Island, South Bangka District - Ayu, Citra; Adibrata, Sudirman; Muftiadi, M. Rizza (Yayasan Serumpun Karang Konservasi, 2024)
Biota plays a role in reef coral is megabenthos . Megabenthos is a large benthic biota more of 1cm and has Power adaptation to condition environment . Benthic biota usually found at the bottom waters like ecosystem reef coral and fields seagrass . Waters Island Pongok own diversity biological abundant sea _ so that made source search society in general working as a fisherman with method netting, fishing and doing arrest with another way . Apart from that, some fisherman Still use tool catch those who don't friendly environment like use bomb and shoot For catching fish. Megabenthos data collection use method Benthos Belt Transect and reef data collection coral use method Underwater Photo Transect . Research results in Water Island Pongok 12 species were found of the 6 families found in the waters Island Pongok . Density value megabenthos found _ range between 0.007-1.257 ( ind /m²) which is dominated by species Diadem setosum with average value _ amounted to 0.688 ( ind /m²), whereas density Lowest is in the species Drupella cornus , Linckia multifora and Trochus niloticus with the average value density 0.002 ( ind /m²). Percentage cover reef coral live on the Island Pongok ranges between 28.67%-63.87% in Medium to Good category . Analysis results Principal Component Analysis (PCA) was obtained results density highest that is Correlated diadema _ with temperature with mark the correlation is 1,000 and temperature namely 0.825, next clams correlated with pH and value the correlation is 0.465 and pH 0.982. From these two biota categorized as correlated perfect with physical and chemical parameters waters. Connection density megabenthos with form growth reef coral density megabenthos highest at the location study is species Diadem sp . which is correlated tall with Dead Coral Algae (DCA) with mark the correlation is 0.998. Density megabenthos Lowest is Correlated Drupella _ tall with Dead Coral Algae (DCA) with mark the correlation is 0.998, and Linckia multifora correlated tall with Coral Foliose (CF) with mark the correlation is 0.925.